2009
DOI: 10.1056/nejmoa0805435
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab for Prednisone-Dependent Asthma with Sputum Eosinophilia

Abstract: Mepolizumab reduced the number of blood and sputum eosinophils and allowed prednisone sparing in patients who had asthma with sputum eosinophilia despite prednisone treatment. (ClinicalTrials.gov number, NCT00292877.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
877
2
28

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,265 publications
(948 citation statements)
references
References 12 publications
16
877
2
28
Order By: Relevance
“…IL-5 is a potent therapeutic target due to its causative relationship to eosinophilia. Therapies for asthma targeting IL-5 are currently being re-evaluated, and promising results have been obtained (47)(48)(49)(50). Therefore, innate IL-5-producing cells should be preferable candidates to study allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…IL-5 is a potent therapeutic target due to its causative relationship to eosinophilia. Therapies for asthma targeting IL-5 are currently being re-evaluated, and promising results have been obtained (47)(48)(49)(50). Therefore, innate IL-5-producing cells should be preferable candidates to study allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Wenzel and colleagues first described this 'eosinophil high' severe asthma phenotype when performing bronchial biopsies and showed that it was associated with airway remodeling and risk of near-fatal asthma attacks [15]. Others showed that severe eosinophilic asthma is characterized by frequent exacerbations and often requires systemic corticosteroid treatment for control of the disease [14,16,17]. Persistent airway eosinophilia (with or without neutrophils) is the key characteristic of this asthma subphenotype, which appears to be reasonably stable over time [18].…”
Section: How Is Eosinophilic Asthma Defined?mentioning
confidence: 99%
“…With regard to (sub-) phenotypes, there are indications that anti-IL-5 therapy can lead to moderate improvement in lung function tests and reduced incidence of severe exacerbation in patients with uncontrolled, eosinophilic asthma (54,55), and possibly nasal polyps (56).…”
Section: (Failure Of) Targeted Therapiesmentioning
confidence: 99%